2015
DOI: 10.1038/ajg.2015.233
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Therapeutic Targets in Inflammatory Bowel Disease (STRIDE): Determining Therapeutic Goals for Treat-to-Target

Abstract: Evidence- and consensus-based recommendations for selecting the goals for treat-to-target strategies in patients with IBD are made available. Prospective studies are needed to determine how these targets will change disease course and patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
1,285
2
38

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,552 publications
(1,397 citation statements)
references
References 180 publications
12
1,285
2
38
Order By: Relevance
“…UCEIS is rather complex and time consuming, which makes it less attractive for routine use in daily practice [48]. Currently, the IOIBD consensus group recommends the endoscopic Mayo score in UC because of its ease of use and established predictive value [45,[49][50]. In line with this recommendation we found that more than half of the participants use the Mayo score (0 or ≤ 1) to define MH in UC.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…UCEIS is rather complex and time consuming, which makes it less attractive for routine use in daily practice [48]. Currently, the IOIBD consensus group recommends the endoscopic Mayo score in UC because of its ease of use and established predictive value [45,[49][50]. In line with this recommendation we found that more than half of the participants use the Mayo score (0 or ≤ 1) to define MH in UC.…”
Section: Discussionsupporting
confidence: 62%
“…This is in line with international guidelines that do not advise histological remission as a treatment target [25][26][27]. Also, IOIBD experts agreed upon histological remission as an adjunctive goal that might come into view in the future, in particular in UC [45]. A unified single definition for MH in IBD is lacking.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Post-hoc analyses from clinical trials showed that endoscopic remission or mucosal healing (MH) affected long-term clinical outcomes, and this observation led to a shift toward endoscopic remission being considered one of the goals of treatment. Subsequently, the STRIDE program examined different possible targets in the treatment and monitoring of IBD and proposed multiple targets of clinical and patient-reported outcomes (PROs), as well as endoscopic remission for both CD and UC [5].…”
Section: Early Intervention Treat-to-target and Tight Monitoringmentioning
confidence: 99%